PROFIL TECHNOLOGICAL, PEDAGOGICAL, AND CONTENT KNOWLEDGE (TPACK) GURU KELAS IV SDN BATOK BALI DALAM PEMBELAJARAN TEMATIK DI ERA NEW NORMAL - Raden Alfarouqy Darmawan; Damanhuri; Aan Subhan Pamungkas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The purpose of this research is to find out how the teacher's steps in preparing thematic learning are integrated with the TPACK framework. This study also aims to determine how the thematic learning process has implemented TPACK in class and the results or output after implementing the TPACK integrated learning. This research uses a qualitative approach with descriptive methods. The data collected in this study used structured interviews, routine observations, and documentation. Field findings prove that the Batok Bali elementary teacher is one of the teachers who can be an example for other teachers in integrating TPACK into thematic learning in this new normal era. The results of this study illustrate that the teacher has his way of using technology for learning. The teacher also has strengths and weaknesses when combining technology, pedagogics, and teaching content to increase the effectiveness and efficiency of learning